Evaluation Of A Professionalism Development Program For Tsanawiah Madrasah Teachers In Langkat District (CIPP Model: Context, Input, Process, And Product) - Muamar Al Qadri; Fachruddin Azmi; Siti Halimah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study was to evaluate the Professionalism Development Program for Madrasah Tsanawiyah Teachers in Langkat Regency (CIPP Model: Context, Input, Process, Product). This research technique is qualitative. Teachers, supervisors, and the head of the Medan BDK became research informants. The data comes from primary and secondary sources. Researcher observation, source triangulation, method triangulation, and researcher triangulation are approaches to ensuring the correctness of data. Observations, interviews, and documentation are all forms of data collection. The conclusion that can be drawn from the results of the study and the findings of the analysis of data on the assessment of the professionalism development program for madrasah tsanawiyah teachers in Langkat Regency (CIPP Model: Context, Input, Process, Product) is that the program is implemented according to plan and goes well and according to plan, implementing learning by forming study groups, then practicing and displaying the results made for widyaswara learning designs to encourage training participants to innovate in the future by utilizing multimedia-based learning media, which will continue to develop along with technological updates in the future.